Molecular Surveillance of Multidrug-Resistant Bacteria among Refugees from Afghanistan in 2 US Military Hospitals during Operation Allies Refuge, 2021 - Cole Anderson; Francois Lebreton; Emma Mills; Brendan Jones; Melissa Martin; Hunter Smith; Roseanne Ressner; Sara Robinson; Wesley Campbell; Jason Smedberg; Michael Backlund; Diane Homeyer; et al. (Emerging Infectious Diseases)
In 2021, two US military hospitals, Landstuhl Regional Medical Center in Landstuhl, Germany, and Walter Reed National Military Medical Center (WRNMMC) in Bethesda, Maryland, USA, observed a high prevalence of multidrug-resistant bacteria among refugees evacuated from Afghanistan during Operation Allies Refuge. Multidrug-resistant isolates collected from 80 patients carried an array of antimicrobial resistance genes, including carbapenemases (blaNDM-1, blaNDM-5, and blaOXA-23) and 16S methyltransferases (rmtC and rmtF). Considering the rising transmission of antimicrobial resistance and unprecedented population displacement globally, these data are a reminder of the need for robust infection control measures and surveillance.